Subsidy for input or purchase? Research on government subsidy strategies in land-sea relay aquaculture mode - Huang, Dexing; Gu, Bojun; Fu, Yufang (Frontiers in Marine Science, 2025)
Based on a deep-sea aquaculture system comprising the government, deep-sea aquaculture enterprise, and fry farmers, this paper constructs a two-stage game-theoretic model of land-sea relay aquaculture under three scenarios: no government subsidy, input subsidy, and purchase subsidy. A comparative analysis is conducted to examine the impact mechanisms of different government subsidy strategies on the decision-making behaviors, profits, and social welfare of the members in the land-sea relay aquaculture supply chain. Our findings are as follows: (1) under government subsidy mechanisms, the enterprise adopts differentiated pricing based on the scale of farmers, manifesting as price suppression for small-scale farmers and price elevation for large-scale farmers. Both input subsidy and purchase subsidy effectively incentivize farmers to improve fry quality and expand fry supply. (2) The comparative advantage of government subsidy strategies depends on the revenue-sharing proportion and farming scale constraints. The degree of risk aversion among farmers influences the threshold of the revenue-sharing proportion, which increases as risk aversion intensifies. (3) Based on the revenue-sharing proportion and farming scale constraints, input subsidy and purchase subsidy strategies each possess distinct advantageous intervals. Within these intervals, the government, deep-sea aquaculture enterprise, and fry farmers can achieve incentive compatibility and a multi-win situation. The findings of this study provide a theoretical framework for governments promoting deep-sea aquaculture to formulate effective subsidy policies and for stakeholders to optimize their decisions.